Policy-making for real: Politics and progress in South African health care - A. Fourie; H. C. J. van Rensburg (AOSIS, 1993)
Problems have been accumulating in South African health care for well over three centuries yet when it comes to resolving the crisis by means of appropriate policy measures, one becomes aware of the powers at play and the interests at stake in maintaining the status quo, thus obstructing much initiative in the process of reform.